The design, development and evaluation of cross-platform mobile applications and services supporting social accountability monitoring - Reynell, Edward Robin (Rhodes University, Faculty of Science, Department of Computer Science, 2016)
Local government processes require meaningful and effective participation from both citizens and their governments in order to remain truly democratic. This project investigates the use of mobile phones as a tool for supporting this participation. MobiSAM, a system which aims to enhance the Social Accountability Monitoring (SAM) methodology at local government level, has been designed and implemented. The research presented in this thesis examines tools and techniques for the development of cross-platform client applications, allowing access to the MobiSAM service, across heterogeneous mobile platforms, handsets and interaction styles. Particular attention is paid to providing an easily navigated user interface (UI), as well as offering clear and concise visualisation capabilities. Depending on the host device, interactivity is also included within these visualisations, potentially helping provide further insight into the visualised data. Guided by the results obtained from a comprehensive baseline study of the Grahamstown area, steps are taken in an attempt to lower the barrier of entry to using the MobiSAM service, potentially maximising its market reach. These include extending client application support to all identified mobile platforms (including feature phones); providing multi-language UIs (in English, isiXhosa and Afrikaans); as well as ensuring client application data usage is kept to a minimum. The particular strengths of a given device are also leveraged, such as its camera capabilities and built-in Global Positioning System (GPS) module, potentially allowing for more effective engagement with local municipalities. Additionally, a Short Message Service (SMS) gateway is developed, allowing all Global System for Mobile Communications (GSM) compatible handsets access to the MobiSAM service via traditional SMS. Following an iterative, user-centred design process, a thorough evaluation of the client application is also performed, in an attempt to gather feedback relating to the navigation and visualisation capabilities. The results of which are used to further refine its design. A comparative usability evaluation using two different versions of the cross-platform client application is also undertaken, highlighting the perceived memorability, learnabilitv and satisfaction of each. Results from the evaluation reveals which version of the client application is to be deployed during future pilot studies.
Keywords: Uncatalogued